The dynamization of Uruguayan agribusiness chains in the context of global commercial expansion (2001-2019) - Bartesaghi, Ignacio (2021)
World agro-industrial production and trade has registered a significant increase in this century. Some Latin American countries, especially in South America, have repositioned themselves as important suppliers of agricultural products. Although the expansion has multiple causes, the accelerated economic growth that the Asia-Pacific region has shownin the last twenty years, driven mainly by China, as well as other regions and emerging countries, has been the basis ofthis process. In this context, Uruguay is one of the South American countries that has shown significant dynamism. This article analyzes how this country, historically agro-exporter, accompanied the expansion of production and world trade based on agriculture, developing its links with the external market from its main industrial chains related to the production of soy, forestry, meat, rice, and dairy products. The key of this process involved, among other things,a special reorganization of agricultural activities, the attraction of foreign direct investment, as well as powerful transformations in terms of technological innovation and agribusiness management.